Unemployment insurance and the business cycle: prolong benefit entitlements in bad times? - Stéphane Moyen; Nikolai Stähler (Deutsche Bundesbank, 2009)
The aim of this paper is to study the optimal duration of unemployment benefit entitlement duration across the business cycle. We wonder if the entitlement duration should be prolonged in bad and shortened in good times. Because of consumption smoothing, such a countercyclical policy can be welfare-enhancing as long as it does not affect labor market adjustment too severely or even helps to reduce inefficiencies there. If, however, the labor market is quite inflexible already, procyclical behavior may be preferable. In a calibrated dynamic business cycle framework, we find that countercyclical benefit entitlement duration may be preferable in the US but not in Europe.
Keywords: E32; G00; E62; 330; Unemployment insurance; entitlement duration; business cycle; Arbeitslosenversicherung; Dauer; Konjunkturelle Arbeitslosigkeit; Arbeitsmarktflexibilisierung; Europa; USA